EVALUASI PROGRAM PENGEMBANGAN PEMASARAN PARIWISATA - Febri Yuliani, Yaumil Hurriyati, Sujianto, (Jurnal Ilmu Administrasi Negara, 2019)
Evaluation of Tourism Marketing Development Program. The purpose of this research is to find out the evaluation of tourism marketing development programs in Kuantan Singingi Regency. The method used is a qualitative descriptive approach, primary data obtained from interviews and observations and secondary data obtained from the collection of data and from documents. The research informants were the Head of the Office, Head of Section, Head of Subdivision, Head of Section, Community and journalists. Data analysis starts from presenting, reducing and drawing conclusions. The results of the study indicate that the tourism marketing development program benefits the community. In conclusion, these activities provided benefits in the form of opening jobs, earning income from the regional treasury, making the district singing alternative singing places, and describing business opportunities for the community.